Assessing Integrated Quality Management Implementation in Early Childhood Education Institutions: A Quantitative Survey from Indonesia - Dwi Prasetiyawati Diyah Hariyanti; Muniroh Munawar; Asep Ardiyanto; Coryza Nursyahbani (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
This study aims to assess the level of implementation of Integrated Quality Management (IQM) in Early Childhood Education (ECE) institutions and to identify strengths and variations across different institutional dimensions. The study employed a descriptive quantitative survey design. Data were collected from 100 accredited ECE institutions in Semarang City, Indonesia, using a structured questionnaire consisting of 20 items covering seven IQM dimensions. Data analysis was conducted using descriptive statistics to examine mean scores, variation, performance categories, and rankings for each dimension. The results indicate that the overall level of IQM implementation falls within the “good” category (M = 3.15; SD = 0.29). The learning process dimension shows the highest level of implementation, while quality culture has the lowest mean score and the highest variation. Most institutions are categorized as “Good” and “Very Good,” indicating relatively homogeneous quality management practices among accredited institutions, although variations remain in organizational culture and support systems. These findings suggest that while pedagogical quality has been well managed, strengthening quality culture remains a key challenge. Enhancing leadership capacity, internal quality assurance systems, and continuous improvement mechanisms are essential to improving IQM implementation in ECE. This study provides comprehensive empirical evidence on IQM implementation in ECE within a developing country context and contributes to the global discourse on quality assurance and educational management.